Thermally stimulated relaxation processes in two-component solid films of nitrogen-ethanol (International Journal of Mathematics and Physics, 2014)
Experimental study of relaxation processes in solid solutions of nitrogen-ethanol observed in the process ofraising the temperature of the film is carried out. Our previous studies have found that the state of the film is notstable. The increase of cry matrix temperature leads to changes in the vibrational spectrum of ethanol. This articlefocuses on determining the effect of ethanol concentration in the nitrogen matrix on the investigated relaxationprocesses. Measurements were carried out in a temperature range from 12 to 40K, the pressure in the vacuumchamber was less than 5×10-8Torr. The concentration of ethanol in nitrogen was varied in the range from 0.5% to 3%.Conclusions are made based on the analysis of thermo grams and said that increase the concentration of ethanol innitrogen leads to the beginning of the relaxation processes at lower temperatures. This is explained by the presence innitrogen cryomatrix of ethanol polyaggregates with larger size.